Pomegranate peel film-forming systems for ruminants’ mastitis prophylaxis: Physicochemical analysis and in vitro and in vivo biological assays - de Paula, Geanne Aparecida [UNESP]; de Melo, Rita Cristina Gonçalves; Fernandes, Fábulo Junior Nogueira; Manhães, Bruno Colli; de Souza Figueredo, Iago Cesar; Donatele, Dirlei Molinari; Almeida, Marco Túlio Costa; Carreira, Lílian Gasparelli; Severi, Juliana Aparecida; Chorilli, Marlus [UNESP]; Resende, Juliana Alves; Villanova, Janaina Cecília Oliveira (Elsevier, 2025)
Mastitis, an inflammatory condition affecting the mammary gland of lactating animals, leads to significant physicochemical and microbiological alterations in milk, compromising its quality and safety for both human and animal consumption. Current treatment options are costly and contribute to the growing issue of antimicrobial resistance among the pathogens responsible for this disease. This study aimed to prepare and evaluate the quality of in situ film-forming solutions (FFS) and films prepared from them [which containing dry pomegranate peel extract (PPE)] for mastitis prophylaxis. Overall, 17 formulations were prepared with different types and concentrations of polymers, of which only four incorporated PPE in their 1.25, 2.5, and 3.75 % m/m concentrations. Analyses were conducted on the chemical composition and total phenol content of the pure extract. In the film-forming solutions, the following parameters were evaluated: appearance, pH, viscosity, film drying time on the skin, total phenol content, and in vitro antimicrobial activity against ATCC strains as well as both sensitive and resistant clinical strains of Staphylococcus aureus isolated from bovine mastitis. An in vivo study was also performed using Santa Inês sheep. For the films produced by the casting solvent technique, additional evaluations included average weight, thickness, moisture content, hemolysis index, and structural and thermal characteristics using XRD, FTIR, TGA, and DSC analyses. Formulation N2, containing 18 % m/m of poly(vinyl alcohol), 0.5 % m/m of sodium polyacrylate, and 2.5 % m/m of the extract, had its in vitro antimicrobial activity confirmed, showing adequate pH, viscosity, and time drying values, in addition to the higher phenolic content, being considered promising for the intended purpose. Results suggest that pomegranate peel film-forming systems can offer a potential prophylactic strategy to treat bovine mastitis and other infections caused by antibiotic-resistant Staphylococcus aureus strains.